2008
DOI: 10.1159/000139659
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Antiplatelet Pre-Treatment on the Risk of Symptomatic Intracranial Haemorrhage after Intravenous Thrombolysis

Abstract: Background: The influence of antiplatelet agents (AP) in the development of a symptomatic intracranial haemorrhage (SICH) after intravenous rt-PA is not well known. We assessed the hypothesis that pre-treatment with AP may increase that risk. Methods: We studied data from consecutive patients with ischaemic stroke treated with intravenous rt-PA within the first 3 h after symptom onset. We recorded the antecedent of any AP therapy previous to thrombolysis. A follow-up CT was performed routinely 24–36 h after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 83 publications
(55 reference statements)
0
27
0
Order By: Relevance
“…The outcomes of study quality assessment are as follows: 8 studies scored 9 (Xian et al,29 Pan et al,25 Meurer et al,24 Ibrahim et al,20 Dorado et al,19 Diedler et al,18 Cucchiara et al,16 and Uyttenboogaart et al13), 3 studies scored 8 (Bluhmki et al,15 Bravo et al,12 and Tanne et al9), and 7 studies scored 7 (Meseguer et al,27 Watson‐Fargie et al,28 Lindley et al,26 Martí‐Fàbregas et al,11 Schmülling et al,10 Šaňák et al,21 and Hermann et al17). Those scores served as differentiators in a subgroup analysis that divided studies into 2 groups (NOS >7 and NOS ≤7).…”
Section: Resultsmentioning
confidence: 99%
“…The outcomes of study quality assessment are as follows: 8 studies scored 9 (Xian et al,29 Pan et al,25 Meurer et al,24 Ibrahim et al,20 Dorado et al,19 Diedler et al,18 Cucchiara et al,16 and Uyttenboogaart et al13), 3 studies scored 8 (Bluhmki et al,15 Bravo et al,12 and Tanne et al9), and 7 studies scored 7 (Meseguer et al,27 Watson‐Fargie et al,28 Lindley et al,26 Martí‐Fàbregas et al,11 Schmülling et al,10 Šaňák et al,21 and Hermann et al17). Those scores served as differentiators in a subgroup analysis that divided studies into 2 groups (NOS >7 and NOS ≤7).…”
Section: Resultsmentioning
confidence: 99%
“…There are 2 potentially modifiable baseline clinical variables associated with post-rtPA hemorrhage, increased blood glucose, and increased blood pressure. Neither the lowering of blood glucose 29 nor the lowering of blood pressure 30 is associated with less death or disability after acute stroke in completed randomized trials, but it is possible that correction of increased blood pressure or glucose might mitigate the increased risk of ICH with rtPA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It recommended against starting antiplatelet (mono-or dual-therapy) or glycoprotein IIb/IIIa inhibitors in addition to IV-tPA in isolated AIS cases. Several studies have suggested increased risk of intracranial hemorrhage with the use of antiplatelet, especially dual antiplatelet therapy with IV-tPA, but have not shown to adversely influence clinical outcome (45)(46)(47)(48). The increased risk of intracranial hemorrhage with these antiplatelet is likely balanced by the beneficial effect of increased reperfusion or decreased risk of vessel re-occlusion, and these antiplatelets may not by themselves increase the risk of intracranial hemorrhage but makes one worse if it occurs (47).…”
Section: Management Of Simultaneous CCImentioning
confidence: 99%